Absolute abundance and relative scarcity: Announced policy, resource extraction, and carbon emissions - Corrado Di Maria; Sjak Smulders; Edwin van der Werf (Fondazione Eni Enrico Mattei (FEEM), 2008)
We study the effectiveness of climate change policy in a model with multiple non-renewable resources that differ in their carbon content. We find that, when allowing some time between announcement and implementation of a cap on carbon dioxide emissions, emissions from non-renewable energy sources increase at the time of announcement. There are two channels behind this effect. First, since a binding constraint on emissions restricts energy use during some period of time, more must be extracted during other periods. Second, since low carbon energy sources are relatively more valuable when the policy is implemented, it is optimal to conserve them ahead of enforcement. This might induce a switch to high-carbon resources before the policy is implemented.
Keywords: Q31; Q41; Q54; Q58; 330; Climate Policy; Non-renewable Resources; Announcement Effects; Scarcity; Order of Extraction